Communication Between Parental and Developing Genomes During Tetrahymena Nuclear Differentiation Is Likely Mediated by Homologous RNAs - Chalker, Douglas L. (Genetics Society of America, 2005)
Approximately 6000 DNA elements, totaling nearly 15 Mb, are coordinately excised from the developing somatic genome of Tetrahymena thermophila. An RNA interference (RNAi)-related mechanism has been implicated in the targeting of these germline-limited sequences for chromatin modification and subsequent DNA rearrangement. The excision of individual DNA segments can be inhibited if the homologous sequence is placed within the parental somatic nucleus, indicating that communication occurs between the parental and developing genomes. To determine how the DNA content of one nucleus is communicated to the other, we assessed DNA rearrangement occurring in wild-type cells that were mated to cells that contained the normally germline-limited M element within their somatic nuclei. M-element rearrangement was blocked in the wild-type cell even when no genetic exchange occurred between mating partners, a finding that is inconsistent with any genetic imprinting models. This inhibition by the parental somatic nucleus was rapidly established between 5 and 6 hr of conjugation, near or shortly after the time that zygotic nuclei are formed. M-element small RNAs (sRNAs) that are believed to direct its rearrangement were found to rapidly accumulate during the first few hours of conjugation before stabilizing to a low, steady-state level. The period between 5 and 6 hr during which sRNA levels stabilize correlates with the time after which the parental genome can block DNA rearrangement. These data lead us to suggest that homologous sRNAs serve as mediators to communicate sequence-specific information between the parental and developing genomes, thereby regulating genome-wide DNA rearrangement, and that these sRNAs can be effectively compared to the somatic genome of both parents.